Development of Physics Worksheet based on STEM integrating Engineering Design Process (EDP) through Guided Inquiry Model to Improve Students’ Critical Thinking - Syukri, Muhammad; Herliana, Fitria; Maryono, Maryono; Ngadimin, Ngadimin; Artika, W. (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aimed to develop a physics worksheet based on STEM integrating Engineering Design Process (EDP) through the guided inquiry model to improve students' critical thinking in learning physics. The research approach used R&D using the ADDIE model, namely: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The data collected was in the form of worksheet eligibility data and critical thinking instruments by experts, and response questionnaires given to five physics teachers at a senior high school in Kutacane. Data analysis using percentage descriptive analysis. The results of the worksheet eligibility test by experts show a percentage score of 79.5%, which is the feasible category, and a critical thinking instrument score of 83.3%, which is the very feasible category. Teachers’ response results show the percentage of suitability indicators of the worksheet with the EDP model step through the guided inquiry model was 91.6% and the EDP model step suitability indicator with critical thinking ability was 93.6%, both of which were included in very valid qualifications. It could be concluded that a worksheet based on STEM integrating the Engineering Design Process (EDP) through the Guided Inquiry Model is appropriate for use to improve students' critical thinking skills in learning physics.